44.8k views
5 votes
Helpppppppppppppppppppp

Helpppppppppppppppppppp-example-1
User Walnutmon
by
6.0k points

1 Answer

6 votes
The quadratic formula is

x= (-b\pm √(b^2-4ac) )/(2a).

For the equation
4x^2-3x+9=2x+1, we must first convert it into standard form
ax^2+bx+c=0. We see it is
4x^2-5x+8=0. From this, our coefficients are
a=4, b=-5 and
c=8.

We plug these coefficients into the quadratic formula.


x= (-(-5)\pm√((-5)^2-4(4)(8)) )/(2(4)) \\ \\ \\ \\ x = (5\pm√(-103))/(8) \\ \\ \\ \\ x = (5\pm\ i√(103))/(8)

The answer is C.
User SunAwtCanvas
by
5.6k points